Sharing economy as an emerging global trend. The case of OFO in The People's Republic of China. - Medvedeva, Alexandra (2018)
This study is dedicated to investigating the sharing economy, a revolutionary trend happening worldwide and involving each of us. After discovering the main general patterns of the phenomenon, the research is narrowed to the size of one particular country. The choice of The Peoples Republic of China is pre-determined by personal interest, the scale and specific local characteristics of the trend, which were highlighted in the study. Furthermore, the detailed analysis of the ofo case, the Chinese leading bike-sharing platform, was used as a tool to reveal and understand the main operational patterns of the sharing economy players in general. The value and usefulness of the findings and lessons drew on this particular case, lay in applicability to the other companies, involved in the sharing economy.